Analisis Dampak Kepemilikan Hunian Terhadap Kondisi Sosial Ekonomi Masyarakat Di Perumahan Griya Bangun Tomohon Lestari I Dan II Kecamatan Tomohon Selatan Kota Tomohon - Pongoh, Dianne Jilly Fioline; Rumagit, Grace Adonia Josefina; Rengkung, Leonardus Ricky (Sam Ratulangi University, 2023)
This study aims to analyze the impact of residential ownership on the socio-economic conditions of the people in Griya Bangun Tomohon Lestari I and II Housing, Tomohon Selatan District, Tomohon City and to analyze the income of residents of Griya Bangun Tomohon Lestari I and II Housing, Tomohon Selatan District, Tomohon City before and after occupying housing. This research was conducted from March to May 2023. The selection of respondents was carried out purposively (purposive sampling). The data used in this study are primary data and secondary data. Primary data was obtained through direct interviews with respondents using a questionnaire as a data collection tool, which contains questions related to socio-economic aspects. Secondary data was obtained from the publications of related agencies, such as BPS Kota Tomohon, Public Housing and Settlement Areas Office of Tomohon City, as well as literature related to this research. The results of the study show that there is an impact of residential ownership on social conditions for residents in Griya Bangun Tomohon Lestari I and II Housing Housing, namely the formation of religious, community and governmental institutional social activities. In the aspect of income for residential ownership in Griya Bangun Tomohon Lestari I and II Housing Housing, there was a significant increase in income after the occupants occupied houses in Griya Bangun Tomohon Lestari I and II Housing.